Uncertainty quantification for linear elastic bodies with two fluctuating input parameters. Issue 1 (21st October 2015) - Dridger, Alex; Caylak, Ismail; Mahnken, Rolf
Abstract: In this work, we present a numerical method for solving partial differential equations (PDEs) with stochastic coefficients for a linear elastic body. To this end, a stochastic finite element method is applied. We distinguish two different cases for an isotropic material with two fluctuating input parameters in order to analyse the optimal choice of input parameters. Using the GALERKIN projection, the final stochastic equation system is reduced to a system of deterministic PDEs. Subsequently, the solution is determined iteratively. Finally, a numerical example for a plate with a ring hole is presented. (© 2015 Wiley‐VCH Verlag GmbH & Co. KGaA, Weinheim)